The Role of Instagram Post Type Towards Audience Engagements - Prakoso, Abdi Setya; Iskandar, Budi Permadi (Journal of Business and Management, 2015)
Abstract: According to the AIDA model, every message posted on Instagram should have been able to get the audience’s attention, which is needed to finally get the audiences to action. To know what kind of post that able to pull the audience’s attention, this research generated several post types that were usually being used in Instagram. The post types that act as the main variable are: Extraordinary, Humor and Touching. The research findings show that in Y generation Instagram user, the Humor post type proved to be the best generally. Which then the research findings suggest that the humor post type is recommended to be used as the content of Instagram post. Keywords: Social Media, Digital Marketing, Marketing Strategy, Instagram.